2016
DOI: 10.5222/buchd.2016.209
|View full text |Cite
|
Sign up to set email alerts
|

Five years of experience in transient hypogammaglobulinemia of infancy

Abstract: ÖZAmaç: Süt çocuğunun geçici hipogamaglobulinemisi (SÇGH), immunoglobulin sentezindeki gecikmeden kaynaklanan, yaşla birlikte tamamen düzelen geçici primer immün yetmezliktir. Bu çalışmada, hipogamaglobulinemi ön tanısı ile izlenen ve SÇGH tanısı alan olgular retrospektif olarak değerlendirildi. 'sı ( %3,1) her ikisini almıştı. Olgular düzelme yaş gruplarına göre gruplandırıldığında, enfeksiyon sıklığı, klinik prezentasyon, aşı yanıtı, İV gamaglobülin replasmanı ve antibiyotik profilaksisi açısından gruplar ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…In the study of Yorulmaz et al, the age at diagnosis of THI varied between 8 months and 48 months, with a mean of 24.6±11.3 months; Karaman et al found the mean age at diagnosis to be 11.7±7.0 months, with a median of 10 months. In their study involving 30 patients, Dogu et al reported the age of diagnosis as 6-46 months (15 below 24 months, 12 24-36 months, 3 36-45 months), and the mean age was 22.5 months [17][18][19] . In our study, the mean age of THI detection in children presenting with chronic cough was 21.73 ± 11.50 months; min -max: 9 -47 months, which was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Yorulmaz et al, the age at diagnosis of THI varied between 8 months and 48 months, with a mean of 24.6±11.3 months; Karaman et al found the mean age at diagnosis to be 11.7±7.0 months, with a median of 10 months. In their study involving 30 patients, Dogu et al reported the age of diagnosis as 6-46 months (15 below 24 months, 12 24-36 months, 3 36-45 months), and the mean age was 22.5 months [17][18][19] . In our study, the mean age of THI detection in children presenting with chronic cough was 21.73 ± 11.50 months; min -max: 9 -47 months, which was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%